Problematika Reforma Agraria pada Tanah Redistribusi Bekas HGU Tratak, Batang - Koes Widarbo (Sekolah Tinggi Pertanahan Nasional, 2021)
The redistribution of land as a means of agrarian reform in Trumben Village, Bandar District, Batang, Central Java Province comes from the former HGU No.1 Tratak. The former HGU was successfully processed into State General Reserves Land (TCUN), then became Landreform Object Land covering an area of ?79.8410 hectare since December 11th, 2015. The object was given to 425 heads of farmer families who had been working on the land. Each farmer receives one plot of land and cannot be transferred without hot official permits. Post-land redistribution, since 2018 the construction of Study Education Outside the Main Campus (PSDKU) UNDIP has begun. In line with this, problems arise, including the transfer of redistribution land ownership to external parties without permission, and the existence of agricultural land parcels for residential houses in the redistribution area. The purpose of this research is to see whether the UNDIP campus construction occurs in the rules of land redistribution transfer and how the alternative solutions to the existing problems. This study used an empirical juridical method with qualitative descriptive data analysis. The conclusion of this research is that the PSDKU development has an impact on the transfer of ownership and changes in the use of agricultural land to non-agricultural.Keywords: agrarian reform, former HGU Tratak, illegal housing Intisari: Redistribusi tanah sebagai salah satu wujud penyelenggaraan reforma agraria di Desa Trumben, Kecamatan Bandar, Kabupaten Batang, Provinsi Jawa Tengah berasal dari bekas HGU No. 1 Tratak. Bekas HGU tersebut kemudian diproses menjadi Tanah Cadangan Umum Negara (TCUN), dan selanjutnya ditetapkan menjadi Obyek Landreform seluas 79,8410 hektar sejak Tanggal 11 Desember 2015. Objek tersebut diberikan kepada 425 kepala keluarga petani yang selama ini menggarap tanah tersebut. Masing-masing petani menerima satu bidang tanah Hak Milik (HM) dan tidak boleh dialihkan tanpa izin pejabat yang berwenang. Pasca redistribusi tanah tersebut, sejak tahun 2018 telah dimulai pembangunan Pendidikan Studi Di luar Kampus Utama (PSDKU) UNDIP. Sejalan dengan hal tersebut timbul permasalahan, antara lain adanya peralihan kepemilikan tanah redistribusi kepada pihak eksternal tanpa izin, serta adanya pengkaplingan tanah pertanian untuk rumah tinggal dalam area redistribusi tersebut. Tujuan penelitian ini adalah untuk mengetahui apakah pembangunan kampus UNDIP mengakibatkan terjadinya pelanggaran terhadap aturan peralihan tanah redistribusi tersebut serta bagaimana alternatif solusi dari permasalahan yang ada. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan yuridis empiris. Kesimpulan dari penelitian ini adalah pembangunan PSDKU berdampak pada peralihan kepemilikan dan perubahan penggunaan tanah pertanian menjadi non pertanian.Kata Kunci; Reforma Agraria, Bekas HGU Tratak, dan perumahan illegal